Preparation, characterization, and properties of acrylonitrile butadiene styrene/multi walled carbon nanotubes nanocomposites - Mohammadsalih, Zaid G.; Abdulameer, Ameer F.; Sadeq, Noor S.; Abbas, Lamiaa K.; Salit @ Sinon, Mohd Sapuan (Springer Science and Business Media, 2024)
The promotion of different properties of polymers has become a substantial worldwide objective for different counterparts in industry and academia. In this work, different loadings of multi walled carbon nanotubes (MWCNTs) were employed to reinforce acrylonitrile butadiene styrene (ABS) to prepare polymer nanocomposites. The employed loadings by solution blending approach were (0.1, 0.5, 1.0, and 5.0) wt. %. FTIR and XRD were utilized to investigate the chemical interaction and crystal structure; respectively. The morphological investigation performed by scanning electron microscopy (SEM) showed the nature of the neat polymer, the dimensions and orientations of the nanotubes, and the good dispersion of the nanotubes within the polymer for the loadings up to 1.0 wt. %. As a result of this good dispersion, thermal properties represented by thermal degradation temperature (Td) and glass transition temperature (Tg) were improved. Furthermore, Young's modulus and tensile strength for the nanocomposite of 1.0 wt. % were enhanced by 87% and 46%, respectively as compared to the neat polymer.